PELATIHAN STRATEGI PEMASARAN DAN PENGEMASAN PRODUK UMKM UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Viarani, Suci Oktri; Akbar, Addin; Sardani, Rizaldi; Mufti, Wahyu Fitrianda; Ramadian, Demi (JURNAL PENGABDIAN MAHAKARYA MASYARAKAT INDONESIA, 2024)
One of the cassava processing businesses that are mostly carried out by the community in Agam Regency, especially in Kamang Magek District is making cassava crackers or better known as Kerupuk Kamang. This cassava crackers business is usually managed by the Home Industry or Small and Medium Industry groups. The marketing process currently carried out is by selling the production of cassava crackers to traditional markets and local distributors, besides that the cassava crackers sold are still in the form of kilos and do not have attractive packaging so that the selling price of cassava crackers is lower. This has an impact on the profits obtained by MSME in the Kamang Magek District, Agam Regency to be small. So that in order to get more profit or income, these MSME must be able to develop marketing and packaging of their products so that more markets can be reached. For this reason, it is necessary to provide briefing/counseling on how to carry out a good marketing strategy, in addition to providing knowledge related to the packaging process that can attract the attention of consumers. As a result of this activity, the community gained new insights regarding good marketing strategies to increase revenue and attract customers, such as making products of various flavors, using product labels/product brands, attractive packaging, promotions with social media and P-IRT permits.